2018
DOI: 10.3389/fendo.2018.00491
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Splicing Is the Pathogenicity Mechanism of the p.Glu314Lys Variant in CYP11A1 Gene

Abstract: Context: The cholesterol side chain cleavage enzyme (CYP11A1) catalyzes the conversion of cholesterol to pregnenolone, the first rate-limiting step of steroidogenesis. CYP11A1 mutations are associated with primary adrenal insufficiency (PAI) as well as disorders of sex development (DSD) in 46,XY patients.Objective: To define the pathogenicity mechanism for the p.Glu314Lys variant, previously reported, and found in four additional patients with CYP11A1 deficiency.Subjects and Methods: DNA of four patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…The partial nature of P450scc deficiency in this family is consistent with most of the published cases with similar genetic findings (19,24,25,26).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The partial nature of P450scc deficiency in this family is consistent with most of the published cases with similar genetic findings (19,24,25,26).…”
Section: Discussionsupporting
confidence: 91%
“…To date, fewer than 40 patients with P450scc deficiency have been reported. Classic deficiency presents with severe earlyonset adrenal insufficiency in the neonatal period and female external genitalia in 46,XY individuals (11,13,14,15,16,17,18,19). Partial defects result in late-onset adrenal insufficiency or glucocorticoid insufficiency alone, associated with either normal genitalia or variable degrees of underandrogenisation (11,15,19,20,21,22,23,24,25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis has revealed that many European individuals and families of European ancestry with this condition are compound (double) heterozygous for a c.940G > A variant (rs6161) on one allele of CYP11A1 and a severely disruptive change on the other allele (Figure A) . Although the c.940G>A variant is predicted to cause a benign protein change (p.E314K), detailed molecular studies have shown that it generates a novel splice site so that missplicing occurs . This variant is carried by approximately 1:140 people of European descent, but is likely to cause adrenal insufficiency only when inherited with a very rare disruptive change on the other allele.…”
Section: Nonclassic Steroidogenic Disorders: Star and Cyp11a1mentioning
confidence: 99%
“…64 Although the c.940G>A variant is predicted to cause a benign protein change (p.E314K), detailed molecular studies have shown that it generates a novel splice site so that missplicing occurs. 64,65 This variant is carried by approximately 1:140 people of European descent, but is likely to cause adrenal insufficiency only when inherited with a very rare disruptive change on the other allele. Partial CYP11A1 insufficiency can also occur in other populations, such as due to the p.R451W variant common in central Turkey.…”
Section: Nonclassic Cyp11a1 Deficiencymentioning
confidence: 99%